The Effect of Health Education about Realizing Using Demonstration Methods on Young Women's Efforts to Detect Early Breast Cancer at Riyadlus Sholihin Vocational High School Probolinggo Regency Probolinggo Regency Pamatan in 2022 - Septi Kurniawati Cahyaning Putri; Yessy Nur Endah Sary; Homsiatur Rohmatin (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Breast cancer arises as a result of abnormal cells forming in the breast at an uncontrolled and irregular rate. Breast cancer can spread to other organs such as the lungs, liver, and brain through the blood vessels. The purpose of the study was the effect of health education on BSE with a demonstration method on the efforts of young women in early detection of breast cancer at SMKI Riyadlus Sholihin Pamatan Tongas, Probolinggo Regency in 2022. This type of research is quantitative research, with the research method of Pre Experimental Design. The sample in this study was 28 respondents using accidental sampling and then it was carried out by filling out a questionnaire. Then the data was processed using SPSS 20 for windows starting with the Wilcoxon test. The results of the analysis of the effect of health education on BSE with the demonstration method on the efforts of young women in early detection of breast cancer, it was found that knowledge before health education was 16 (57.1%), knowledge after health education was less, which was 16 (57.1%) is good in the amount of 19 (67.9%), the statistical test results obtained a value of p = 0.000 with a significant level of 0.05 (p = 0.000 0.05), then it proves that H1 is accepted which means that there is an effect of health education on BSE with demonstration method for young women's efforts in early detection of breast cancer. Health education is one of the means or efforts that can be used to display health messages and information to be conveyed to young women so that they can increase knowledge which is expected to change behavior in a positive direction or support health.